Does the Internet Make the World Worse? Depression, Aggression and Polarization in the Social Media Age. (December 2021) - Ferguson, Christopher J.
Since the 1990s, the influence of the internet and social media in daily communication has skyrocketed. This has brought both remarkable opportunities and perceived perils. Recent years have seen increases in suicide and mental health concerns, political polarization, and online aggression. Can such phenomenon be connected causally to communication via social media? This article reviews the evidence for perceived deleterious effects of social media on several areas of human welfare, including political polarization, depression and suicide, aggression, and cyberbullying. In addition to examining contemporary evidence from psychological studies, a historical analysis is included to examine whether we truly live in a uniquely difficult time or whether similar patterns of social behavior can be witnessed in other, pre-internet times. It is concluded that evidence may link social media to some negative social outcomes but in ways that are nuanced and complicated, often interacting with user motivations and personalities and situational variables. An increased focus on preregistered, standardized scientific methods and cautious interpretation of effect sizes can help clarify real versus phantom effects of social media.